The Mediation Role of Occupational stress on the Relationship of Organizational Justice to Personnel Performance - Akira Ceria; Muhammad Rasyid Abdillah; Agus Seswandi (Yayasan Education Al Aqsho Modern, 2022)
This study aims to see how the Mediation Role of Occupational stress on the Relationship of Organizational Justice to the Performance of Dumai Police Personnel. In addition, this study will also look at the interaction of the two variables and how organizational justice affects the performance of the Police. This type of research is explanatory research. The population is members of the Dumai City Police, totaling 172 people. Data analysis in this study used SEM-PLS. Based on the data processing, it was found that organizational justice, both distributive, procedural and interactional affected the performance of members of the Dumai Resort Police. In addition, an understanding of organizational justice (distributive, procedural and ineractional) mediates the effect of occupational stress on the performance of members of the Dumai Resort Police. The limitation of this study is that the population is only in Dumai Resort, so it is recommended for further researchers to increase the study population.